2020
DOI: 10.29252/jafm.13.01.30350
|View full text |Cite
|
Sign up to set email alerts
|

CFD-DEM Simulation to Predict the Critical Velocity of Slurry Flows

Abstract: The hydraulic transport of solids has been adopted for many years. However, deposition of the solid particles in the pipe can cause equipment failure, pipeline erosion, and excessive pressure drop, resulting in financial and environmental problems. The critical velocity, also known as critical deposition velocity, is the limit of particle deposition when a moving bed of particles starts to form on the bottom of the pipe. The determination of the critical deposition velocity is an essential step in slurry pipel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In this paper, the CFD-DEM coupling method is used to simulate the collision process between particleparticle and particle-wall in the liquid-solid twophase flow (Januário and Maia 2020). For the calculation of the continuous phase flow field, the RNG k-ε turbulent model is adopted.…”
Section: Cfd-dem Coupling Modelsmentioning
confidence: 99%
“…In this paper, the CFD-DEM coupling method is used to simulate the collision process between particleparticle and particle-wall in the liquid-solid twophase flow (Januário and Maia 2020). For the calculation of the continuous phase flow field, the RNG k-ε turbulent model is adopted.…”
Section: Cfd-dem Coupling Modelsmentioning
confidence: 99%
“…Lately, researchers have shown a growing interest in the CFD-DEM approach. Zhang [23], Januário [24], and others used CFD-DEM methods to study the sediment-laden flow of pipes, involving flow regimes and critical velocity. Nonetheless, the computational resource constraints restrict the applicability of such methods for analyzing slurries containing a high number of particles.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [18] simulated the conveying of solid particles in vertical pipes, and the results showed that the solid volume fraction and axial velocity of liquids and solids all had the maximum value in the middle of the pipeline. Januário et al [19] simulated the critical deposition velocity of various ores, and the results were compared with the experimental data from other studies. Akhshik et al [20,21] studied the transportation mechanism of fluid and cuttings in well-drilling through the CFD-DEM method.…”
Section: Introductionmentioning
confidence: 99%